The Bible : An Introduction, Third Edition - Sumney, Jerry L. (Book collections on Project MUSE., 2021)
What is the Bible? How did it get to us? Why are translations so different? And what influence has the Bible had on culture? From its very first pages, The Bible: An Introduction, Third Edition, offers clear answers to the most basic questions that first-time students and curious inquirers bring to the Bible.Without presuming either prior knowledge of the Bible or a particular attitude toward it, Jerry L. Sumney uses straightforward language to lead the reader on an exploration of the Bible's contents and the history of its writings, showing how critical methods help readers understand what they find in the Bible. Filled with maps, charts, illustrations, and color photographs to enhance the student's experience with the text.This third edition offers a number of revisions and a new section on the deuterocanonical books. Neither polemical nor apologetic, The Bible presents the biblical writings as the efforts of men and women in the past to understand their lives and their world in light of the ways they understood the divine.